Isolation of Flavonoid Compounds from Suren Leaves (Toona sureni) - Lenny, Sovia (Talenta Publisher, 2021)
Isolation of flavonoid compound from Suren leaves (Toona sureni) has been done using the extraction method. The suren leaves extract was separated by using the column chromatography method. The isolated compound results were yellow paste with weight 47 from fraction 55-67 and Rf = 0.44 of eluent n-hexane: ethylacetate 60:40 (v/v). The identification process was analyzed by UV-Vis, FT-IR spectroscopy, and 1H-NMR spectroscopy. The obtained result shows that the isolated compound was isoflavone.